Assessment of DNA strand breakage in streptozotocin-induced diabetic Rats - Siti Balkis Budin; Norfadilah Rejab; Abdul Gapor Mohd Top; Wan Nozaimoon Wan Mohamud; Mokhtar Abu Bakar; Khairul Osman; Jamaludin Mohamed (penerbit ukm, 2005)
This study was conducted to evaluate the oxidative damage in diabetic mellitus induced rats. The evaluation of DNA damage was carried out by the Alkaline Comet Assay using peripheral lymphocyte cells taken from streptozotocin-induced diabetic rats (50 mg/kg) and control rats. The levels of malondealdehyde (MDA), 4-hydroxynonenal (4-HNE), fasting blood glucose (FBG) and HbA1c were also measured. All the induced diabetic rats were hyperglycemic until the end of the study with significantly higher levels of FBG and HbA1c as compared to the control rats. The results showed the percentage of tail DNA and tail moment values were also significantly higher in the diabetic induced rats. The same observations were made on the levels of plasma MDA and 4-HNE. In conclusion, this study indicated that hyperglycemic condition in diabetic induced rats could generate oxidative DNA damage.